The effect of dopamine on the formation of polydopamine-polyacrylamide (PDA-PAM) hydrogel - Tang, Leon Sing Peng (Nanyang Technological University, 2023)
This project intends to investigate the relationship between the amount of dopamine and the mechanical and adhesive properties of polydopamine-polyacrylamide hydrogel. Various weight ratios of dopamine to acrylamide were explored. The hydrogels were synthesized in-house before testing. Tensile test as well as lap-shear tests were conducted to observe the effects of varying amounts of dopamine on the hydrogel. After that, the data would be exported to excel to decipher the data and understand the impact of dopamine on the formation of polydopamine-polyacrylamide hydrogel. The results obtained shows that the mechanical and adhesive properties of the hydrogel samples were closely related to the amount of dopamine. Further approaches to characterize the hydrogels were mentioned to improve the understanding of the effects of dopamine and encourage developments on polydopamine-polyacrylamide hydrogels.